Quality care for patients with tenosynovial giant cell tumor: A multidisciplinary quality improvement initiative. Issue 28 (1st October 2022) - Tap, William D.; Pollack, Seth; Carter, Jeffrey D.; Heggen, Cherilyn; McKinnon, Kelly E.
Abstract : 56 Background: Tenosynovial giant cell tumor (TGCT) is a rare soft tissue sarcoma that is difficult to treat due to location, high risk of recurrence, and potential for significant morbidity. Recent approvals of novel systemic therapies provide new options for patients who may not be candidates for surgery. However, clinical teams may encounter challenges that inhibit prompt referral, quality of life assessment, and effective multidisciplinary care coordination between surgeons and oncologists. Methods: In September 2020, we surveyed multidisciplinary oncology health teams (n = 25) to assess gaps in TGCT diagnosis, clinical care, and multidisciplinary care coordination. To address identified gaps, teams participated in audit-feedback sessions to develop action plans for improvement. To better understand identified gaps, surveys and education were extended to a nationwide audience of providers caring for patients with TGCT (n = 553). Results: In the health teams survey, top challenges identified included differentiating among appropriate treatment management strategies (46%), coordinating care/transitions of care for patients with TGCT (25%), and making a proper TGCT diagnosis (13%). Confidence gaps echoed these challenges, with less than half of providers indicating high/very high confidence (5-point Likert scale) in their ability to distinguish between nodular and diffuse types of TGCT (47%), align treatment decisions with evidence-based guidelines (47%), and recognize and manage adverse events associated with novel therapies (47%). During audit-feedback sessions, teams developed action plans to improve collaboration between interprofessional teams, improve adverse event management, increase education for supportive care, and facilitate earlier referrals to medical oncologists. When healthcare providers nationwide were surveyed, only 13% reported high or very high confidence in differentiating available treatment options for TGCT. Additionally, the top challenges in coordination care for patients with TGCT included poor follow-up/monitoring for disease recurrence (23%), ineffective communication between multidisciplinary team members (20%), and lack of time for patient-centered measures (19%). Conclusions: These findings reveal important challenges in diagnosis, treatment, and multidisciplinary care of TGCT patients. The methods and findings from this study offer key opportunities for scalable interventions to improve care for patients with TGCT.